Neural and behavioral alterations of a real-time interpersonal distance (IPD) development process in differing social status interactions - Huang, Xinxin; Izumi, Shin-Ichi; Suzukamo, Yoshimi (Frontiers in Behavioral Neuroscience, 2022)
Background: Evidence showed neural changes in interpersonal distance (IPD) interaction, and neural activities are affected by relationships (such as friends or strangers). Behavior studies proved that social status strongly affects IPD between two persons. However, how the differing social status impacts neural alterations in the IPD interactions remains unknown. Objectives: The teacher-student relationship is a typical representation of the difference in social status. The present study aims to investigate the IPD performance and brain processes underlying real-time differing social status during the development process from teacher-student interactions. Methods: We designed three within-subject experiments corresponding to the inclusion, control, and affection stages of IPD. Altogether, 38 valid healthy participants participated in three experiments with a teacher (differing social status condition, DS condition) and a peer student (peer social status condition, PS condition) separately. This study employed functional near-infrared spectroscopy (fNIRS) and modified real-time stop-distance paradigms to record IPD performance and neural processes. Results: For IPD performance, significantly larger IPD gaps were shown in the DS condition than in the PS condition, and IPD feedback affected IPD performance. For neural alterations, activated frontopolar area (FPA, BA10), dorsolateral prefrontal cortex (DLPFC, BA9/BA46), and Broca’s area (BA45) were observed across the IPD stages. Importantly, brain activation shifts with the development of IPD. In addition, results showed that differences in Oxy-Hb changes were located in the FPA(BA10), DLPFC (BA9/BA46), and Broca’s area (BA45) between the DS and PS conditions across IPD stages. Additionally, negative correlations were found between Oxy-Hb changes and IPD performance. Conclusions: We propose prefrontal cortex (PFC) and Broca’s area involvement in IPD interactions, initially focusing on evaluation and action periods, and later on IPD-evaluation processes after feedback. In addition, a difference in Oxy-Hb activities implies the complexity of relationships and social status in IPD interactions. Abbreviations: interpersonal distance (IPD); differing social status condition (DS condition); peer social status condition (PS condition); functional near-infrared spectroscopy (fNIRS); oxyhemoglobin (Oxy-Hb); frontopolar area (FPA); dorsolateral prefrontal cortex (DLPFC); prefrontal cortex (PFC)